Study on Biochemical Preparation of Natural and Rare Carbohydrate (Pentoses) - Zakaria Ahmed; Shuranjan Sarkar; Taslima Rahman (Challenges and Advances in Chemical Science Vol. 7, 2021)
Biochemical methods, usually microbial or enzymatic, are suitable for the production of unnatural or rare monosaccharides. D-Arabitol was produced from D-glucose by fermentation with Candida famata R28. D-xylulose can be produced from D-arabitol using Acetobacter aceti IFO 3281. D-Lyxose was produced enzymatically from D-xylulose using L-ribose isomerase (L-RI). Ribitol was oxidized to L-ribulose by microbial bioconversion with Acetobacter aceti IFO 3281 whereas L- ribulose was epimerized to L-xylulose by the enzyme D-tagatose-3-epimerase. L- Lyxose was produced by isomerization of L-RI. Moreover, L-ribose and L-arabinose were prepared biochemically from ribitol by oxidation using Acetobacter aceti IFO 3281 and isomerization using L- RI and L-arabinose isomerase (L-AI), respectively. Other pentoses can be produced as well by cell or enzyme bioconversions. This study provides important information for rare sugar preparation and importance.